Desain Instruksional Berbasis Problem-Based Learning pada Materi SPLDV untuk Meningkatkan Berpikir Kritis Matematis Siswa SMP - Janna Sri Bina Br Barus; Tian Abdul Aziz (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to develop an instructional design based on Problem-Based Learning (PBL) for the topic of Systems of Linear Equations in Two Variables (SLETV), which is effective in enhancing the mathematical critical thinking skills of junior high school students. The research method employed is the Instructional Development Model (IDM), which was implemented up to the development phase only. The subjects of the study were eighth-grade junior high school students.